Evaluating the Effects of Fatigue on Police Patrol Officers in Lowell, Massachusetts, Polk County, Florida, Portland, Oregon, and Arlington County, Virginia, 1997-1998 - Kenney, Dennis Jay ([Verlag nicht ermittelbar], 2001)
This study was undertaken to assess the connections between administratively controllable sources of fatigue among police patrol officers and problems such as diminished performance, accidents, and illness. The study sought to answer: (1) What is the prevalence of officer fatigue, and what are officers' attitudes toward it? (2) What are the causes or correlates of officer fatigue? (3) How does fatigue affect officer safety, health, and job performance? and (4) Can officer fatigue be measured objectively? The final sample was comprised of all sworn, nonsupervisory police officers assigned full-time to patrol and/or community policing functions on the day that data collection began at each of four selected sites: Lowell, Massachusetts, Polk County, Florida, Portland, Oregon, and Arlington County, Virginia. Part 1, Fatigue Survey Data, includes demographic data and officers' responses from the initial self-report survey. Variables include the extent to which the respondent felt hot or cold, experienced uncomfortable breathing, bad dreams, or pain while sleeping, the time the respondent usually went to bed, number of hours slept each night, quality of sleep, whether medicine was taken as a sleep aid, estimated hours worked in a one-, two-, seven-, and thirty-day period, how overtime affected income, family relationships, and social activities, and reasons for feeling tired. Part 2, Demographic and Fatigue Survey Data, is comprised of data obtained from administrative records and demographic data forms. Several measures from the initial self-report survey are also included in Part 2. Variables focus on respondents' age, sex, race, marital status, global score on the Pittsburgh Sleep Quality Index scale, total years as a police officer assigned to any agency and current agency, and total years worked in current shift. Data for Part 3, FIT and Administrative Data, were obtained from administrative records and from the fitness-for-duty (FIT) workplace screener test. Variables include a pupilometry index score and the dates, time, and particular shift (days, evenings, or midnight) the officer started working when the pupilometry test was administered. Part 3 also includes the number of hours worked by the officer in a regular shift or in association with overtime, the number of sick leave hours taken by the officer, and whether the officer was involved in an on-duty accident, injured on duty, or commended by his/her department during a particular shift.